THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON ACADEMIC ACHIEVEMENT OF STUDENTS OF CLASS 2022 IN CATECHETICAL PASTORAL COLLEGE OF ST. JOHN THE APOSTLE JAYAPURA - Helyanan, Maria Avia; Margaretha Seveningsih (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2025)
This study aims to determine the effect of emotional intelligence on the academic achievement of students of the 2022 batch of STPK Santo Yohanes Rasul Jayapura. The method used in this study is a quantitative method, with simple linear regression analysis techniques and coefficient of determination. The population in this study were all 37 students of the 2022 batch of STPK Santo Yohanes Rasul Jayapura. The sample used was 37 students with the basis of saturated sampling technique, namely all members of the population. Data collection techniques used a Likert scale questionnaire, observation, interviews and documentation. Data processing in this study used the SPSS program version 25. In the validity and reliability test stage, it was found that the variable X 23 items were declared valid with a reliability of 0.925 and the variable Y 29 items were declared valid with a reliability level of 0.925. The results of this study indicate a significant effect between emotional intelligence on the academic achievement of students of the 2022 batch of STPK Santo Yohanes Rasul Jayapura with a 5% error rate. It is known that the significance is 0.00 <0.05, so it can be concluded that H1 is accepted and H0 is rejected. It is known that variable X contributes 74.3% to variable Y, while the remaining 25.7% is influenced by other variables not yet examined by the researcher, namely spiritual intelligence, intellectual intelligence, learning behavior, and self-concept.